(untitled) (Faridpur Medical College Journal, 2017)
Neonatal jaundice is observed during 1st week of life in approximately 60% of term infants and 80% of preterm infants. All jaundiced newborns are at potential risk for developing severe hyperbilirubinemia if there is uncontrolled or managed inappropriately. The objective of this study is to compare serum bilirubin level of term and preterm babies. A cross-sectional study was conducted with total of 100 newborns babies who were admitted into neonatal unit, babies from obstetric department and who came for checkup and follow up in neonatal unit of Mymensingh Medical College Hospital, Mymensingh during the period August 2006 to January 2007. In this study, mean gestational age of term babies was 38.9±1.22 weeks and of preterm babies was 34.64±1.05 weeks. Mean bilirubin levels observed in term babies 6.68 and 5.72 mg/dl on day 3 and day 5 respectively. In preterm babies, the mean bilirubin levels were 7.16 and 9.09 mg/dl on day 3 and day 5 respectively. Statistically significant differences were observed in bilirubin level on day 5 in both term and preterm groups (p<0.05). Incidence of jaundice among term babies was 64.0% and among preterm babies was 84.0%. Jaundice developed significantly more among the preterm babies than the term babies (p<0.05). From this study, it can be concluded that in premature infants, the rate of rise in serum bilirubin tends to be the same or a little slower and mean serum bilirubin level was higher than that of term babies. Faridpur Med. Coll. J. Jan 2017;12(1): 5-8